Taxonomic diversity of macroflora vegetation among main stands of the forest of Wanagama I, Gunung Kidul - WIDODO WIDODO; SUTARNO SUTARNO; SRI WIDORETNO; SUGIYARTO SUGIYARTO (Biodiversitas Journal of Biological Diversity, 2010)
Widodo, Sutarno, Widoretno S, Sugiyarto (2010) Taxonomic diversity of macroflora vegetation among main stands of the forest of Wanagama I, Gunung Kidul. Biodiversitas 11: 89-92. The objective of this study is to determine the diversity of taxonomy of macro flora vegetation in the main stands of the forest of Wanagama I in Gunung Kidul, Yogyakarta, Indonesia. Vegetation diversity data can be used as a recommendation for conserving the local biodiversity as well as other planned conservation activities. The nested square sampling method was applied to collect the data required in the research. The size of the nested square was based on species-area curves, as well as theories of other studies. The seven main stands studied were: pine (Pinus merkusii), mahogany (Swieteniamahagoni), kesambi (Schleichera oleosa), teak (Tectona grandis), cajuput (Melaleuca leucadendron), Gliricidia (Gliricidia sepium), and a mixed stand. Each stand was observed four times. The square location was randomly determined based on a contour map of the area. The variables of the study of diversity in terms of taxonomy consist of species, genus, family, and order richness. The results were, then, analyzed statistically using one-way Analysis of Variance (ANOVA) and Turkey’s test. The result of the study shows that the species of the main stands was affected very significantly by the diversity of all level: species, genus, family, and order total richness. The Pine stand has the highest rank in terms of number of species, genus, family, and order richness.Key words: taxonomic diversity, main stands, Wanagama